2007
DOI: 10.1111/j.1447-0756.2007.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal fasting on uterine arterial blood flow

Abstract: Maternal fasting is not associated with significant changes in the uterine artery Doppler flow velocimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
3
21
1
1
Order By: Relevance
“…Consistent with our findings, Mirghani et al [12] showed that fetal breathing movements were absent in all fasting pregnant women included in their study. Hypoglycemia has been found to reduce fetal breathing movements in sheep [14,15].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Consistent with our findings, Mirghani et al [12] showed that fetal breathing movements were absent in all fasting pregnant women included in their study. Hypoglycemia has been found to reduce fetal breathing movements in sheep [14,15].…”
Section: Discussionsupporting
confidence: 94%
“…Human fetal breathing movements are significantly affected by maternal blood glucose level and increase significantly after maternal ingestion of glucose [7]; the maximum rate coincides with the peak maternal plasma glucose concentration [16]. In the present study, the fasting time was 2-4 hours longer than in the study by Mirghani et al [12]. Moreover, in the present study the patients received balanced meals that contained only 30% carbohydrate, while contents of the meals used in the previous studies were either intravenous glucose [7] or were not specified [12,13].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Cependant, cette étude a également montré une baisse de l'urée plasmatique, du cholestérol total, du LDL cholestérol, des protéines totales chez les femmes enceintes qui jeunent par rapport à celles qui ne jeunent pas. Une autre étude sur 36 femmes enceintes jeunant versus 29 autres ne jeunant pas a montré un taux de glycémie plus bas sans effet sur le taux de corps cétonique urinaire [7] ni sur le flux sanguin au niveau de l'artère utérine [8].…”
Section: Les Données De La Littératureunclassified